Comparison of the structures of natural and synthetic Pb-Cu-jarosite-type compounds - Hudson-Edwards, K.; Smith, A.; Dubbin, W.; Bennett, A.; Murphy, P.; Wright, Kathleen (E.Schweizerbart'sche Velagsbuchhandlung, 2008)
Jarosite minerals are effective scavengers of potentially toxic elements such as Pb and Cu, and are abundant in acid rock drainage systems, acid sulfate soils and metallurgical wastes. We used XRD, SEM, and infrared, Raman and X-ray absorption (EXAFS and XANES) spectroscopy to determine the structural differences between natural and synthetic Pb-Cu-jarosites. Differences in the a0 unit cell dimensions for the natural and synthetic samples (7.2288(27) and 7.32088(26) respectively), and c0 unit cell values (34.407(14) and 17.0336(7) respectively) are attributed to different proportions of H3O, Fe and Pb in the jarosite structures. The synthetic Pb-Cu-jarosite has sharper Raman and IR spectra, with narrower and more intense bands, suggesting that it is more crystalline than the natural sample. EXAFS fitting of the Fe and Pb data for the natural and synthetic Pb-Cu-jarosite samples are similar to each other, and are also similar to previously reported EXAFS data for jarosites, suggestingthat Fe occupies the B sites, and Pb the A sites. The natural sample?s Pb EXAFS data are only fitted over a short k-range, however, and the comparison is based on only the first two shells around Pb. Our Cu fits for the natural Pb-Cu-jarosite are similar to the first and third shell fittings for Fe, except that the Cu occupies a tetrahedral rather than an octahedral site (4 O in first shell at r = 1.94?1.95 4 Fe in third shell at r = 3.59?3.60 . In the synthetic Pb-Cu-jarosite, Cu also shares the B site with Fe, butfits of 4 Cu around the Cu atom at a bond distance of 2.60 and XANES evidence also suggest the presence of metallic Cu within the structure. Variations in the structures of the natural and synthetic samples are likely due to their differing chemistries and conditions of formation.